Polyorganosilicone polybasic acid composite hydrogel as well as preparation method and application thereof
By introducing hydrophilic polysilicon acetate into the hydrogel and building a dual network structure using the polyacid replacement strategy, the problem of insufficient mechanical properties of the hydrogel is solved, significantly improving its strength and toughness, and enhancing the biological Compatibility has expanded its application in the field of biomedical science.
Patent Information
- Application Number
- CN202411384547.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
The poor mechanical properties of existing hydrogels, poor wetting and lubricity, limit their application in the biomedical field, especially due to the super hydrophobicity of silicone polymers, which leads to the introduction of hydrogels. Material concentration and dispersion are limited.
By introducing hydrophilic polysilicon acetate and using the polyacid replacement strategy to construct a polysilicon polyacid composite hydrogel, the tensile strength and toughness of the hydrogel are improved, the dual network structure is formed, and biological efficacy is enhanced.
It significantly improves the strength and toughness of the hydrogel, enhances its biocompatibility and mechanical properties, and expands its application potential in the field of biomedical science.
Smart Images

Figure CN119286002A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogels, and in particular relates to a polysilicone polyacid composite hydrogel and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Hydrogel is a typical class of soft and wet materials, which is composed of physically or chemically cross-linked hydrophilic three-dimensional polymer networks permeated with water. It has adjustable physical and chemical properties, such as excellent softness and flexibility, wettability and lubricity, and biocompatibility. Therefore, it has been widely used in many fields such as tissue engineering, drug delivery, organ model manufacturing, and bio-lubricated medical devices.
[0004] Among these hydrogels, single-network hydrogel represented by polyvinyl alcohol (PVA) hydrogel is a physically cross-linked single-component hydrogel with widely adjustable mechanical, structural and physical properties. Due to its excellent biocompatibility, good chemical stability and high hydrophilicity, it has been widely explored for use in biomedical materials. At the same time, PVA hydrogel has smooth properties close to biological soft tissues and has been widely used in many biomedical fields closely related to biological organisms, including corneal implants, contact lenses, artificial menisci, cartilage tissue substitutes, and vitreous substitutes. However, the current single-network hydrogels such as PVA hydrogel are often severely limited in their scope of application due to their poor mechanical properties, wettability and lubricity.
[0005] The introduction of other active substances into hydrogels is believed to be effective in improving the mechanical properties, wettability and biocompatibility of hydrogels and giving them more functions. Introducing silicone polymers with excellent biocompatibility, physiological inertness, non-carcinogenicity and hypoallergenicity into hydrogels can not only improve the basic properties of the material, but also produce countless interesting new properties, including improved mechanical properties, reduced flammability and inflammatory response and excellent biocompatibility. However, the intrinsic super hydrophobicity of silicone polymers greatly limits their feed concentration and dispersibility in hydrogels, and also limits the function of silicone polymer hydrogels in aqueous environments such as in vivo. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a polyorganosilicon acetate composite hydrogel and its preparation method and application. The present invention introduces hydrophilic polyorganosilicon acetate into the hydrogel matrix and constructs a polyorganosilicon polyacid composite hydrogel through a polyacid replacement strategy, the concentration of polyorganosilicon in the hydrogel is increased, and the tensile strength of the hydrogel is much higher than that of traditional hydrogels.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a polysilicone polyacid composite hydrogel, comprising the following steps:
[0009] S1, adding aminopolysiloxane to an organic acid solution, stirring until the aminopolysiloxane is dissolved, and obtaining a hydrophilic polysilicon organic acid salt aqueous solution;
[0010] S2, mixing a hydrophilic polysilicon organic acid salt aqueous solution with a hydrogel matrix to obtain a mixed solution, cross-linking the mixed solution to obtain a single network hydrogel, and immersing the single network hydrogel in an aqueous solution of a polyacid salt to obtain a polysilicon polyacid composite hydrogel.
[0011] Preferably, in step S1, the organic acid includes acetic acid, and the mass ratio of the organic acid to aminopolysiloxane is (0.1-2):1.
[0012] Preferably, in step S1, the molar ratio of amino group to silicon atom in the aminopolysiloxane is (0.1-1):1.
[0013] Preferably, in step S2, the hydrogel matrix includes PVA, gelatin or methacrylated gelatin, the mass concentration of aminopolysiloxane in the mixed solution is 1 to 10 wt.%, and the mass concentration of the hydrogel matrix is 1 to 15 wt.%.
[0014] Preferably, in step S2, the cross-linking method includes freeze-thaw cycle, photo-initiation or thermal-initiation.
[0015] More preferably, the freeze-thaw cycle is specifically placed in an environment of -25°C to 0°C for 1 to 24 hours and then placed in an environment of 0°C to 35°C for 1 to 4 hours, and repeated 1 to 5 times.
[0016] Further preferably, the photoinitiator used for photoinitiation includes 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and the mass of the photoinitiator is 0.5% to 2% of the mass of the hydrogel matrix.
[0017] Preferably, the polyacid salt includes at least one of sodium salt, potassium salt and lithium salt of a polyacid, and the polyacid includes at least one of citric acid, tripolyphosphoric acid and phytic acid.
[0018] In a second aspect, the present invention provides a polysilicone polyacid composite hydrogel obtained by the preparation method described in the first aspect.
[0019] In a third aspect, the present invention provides an application of the polysilicone polyacid composite hydrogel as described in the second aspect in the field of structural materials, photoluminescent devices, intelligent switches, drivers or biomedical materials.
[0020] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0021] Through the polyacid replacement strategy, the HAc in the aminopolysiloxane acetate is replaced by a polyacid, and then cross-linked through ionic interactions to form a network, which is composited with the network formed by the hydrogel matrix to construct a double network structure, thereby improving the strength and toughness of the hydrogel.
[0022] By using aminopolysiloxane acetate, the concentration of aminopolysiloxane in the hydrogel is greatly increased, which is beneficial for the hydrogel to exert its biological efficacy.
[0023] The polyacid replacement strategy can be applied to different hydrogel matrices and is also suitable for different hydrogel cross-linking methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0025] Figure 1 PVA 10 、PVA-APDMS 10 -CA, PVA-APDMS 10 -TA and PVA-APDMS 10 -SEM image of PA;
[0026] Figure 2 PVA 10 、PVA-APDMS 10 -CA, PVA-APDMS 10 -TA and PVA-APDMS 10 -(a) FTIR spectrum, (b) G' and (c) G" of PA;
[0027] Figure 3 PVA 10 、PVA-APDMS 10-CA, PVA-APDMS 10 -TA and PVA-APDMS 10 -PA (a) stress-strain curve and (b) energy dissipation efficiency and toughness diagram, (c) PVA 10 (d) PVA-APDMS 10 -CA, (e)PVA-APDMS 10 -TA and (f)PVA-APDMS 10 - Loading-unloading cycle curve of PA at 300% strain;
[0028] Figure 4 PVA 10 、PVA-APDMS 2.5 -PA, PVA-APDMS 5 -PA and PVA-APDMS 10 -SEM image of PA;
[0029] Figure 5 PVA 10 、PVA-APDMS 25 -PA, PVA-APDMS 5 -PA and PVA-APDMS 10 - (a) FTIR spectrum and (b) rheological spectrum of PA;
[0030] Figure 6 PVA 10 、PVA-APDMS 2.5 -PA, PVA-APDMS 5 -PA and PVA-APDMS 10 - (a) stress-strain curve and (b) energy dissipation efficiency and toughness diagram of PA;
[0031] Figure 7 (a) PVA 10 (b) PVA-APDMS 2.5 -PA, (c)PVA-APDMS 5 -PA and (d)PVA-APDMS 10 -PA loading-unloading cycle curve at 300% strain, (e) PVA-APDMS 10 -PA loading-unloading curves of 5 cycles at 300% strain, (f) PVA-APDMS 10 - Loading-unloading cycle curves of PA hydrogel under strain (50% to 300%);
[0032] Figure 8 For GelMA 5 、GelMA5 +APDMS 5 -TA, GelMA 5 +APDMS 10 -TA and GelMA 5 +APDMS 15 -SEM image of TA;
[0033] Fig. 9 For GelMA 5 and GelMA 5 +APDMS 10 - EDS diagram of TA;
[0034] Fig.10 For GelMA 5 、GelMA 5 +APDMS 5 -TA, GelMA 5 +APDMS 10 -TA and GelMA 5 +APDMS 15 -TA’s (a) photograph, (b) FT-IR spectrum, and (c) rheological diagram. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0036] Example 1
[0037] Take octamethylcyclotetrasiloxane (D 4 , 74.0 g, 0.25 mol), N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (AEAPMDS, 88.7 g, 0.43 mol), deionized water (15.5 g, 0.86 mol) and tetramethylammonium hydroxide (0.05 g, Me 4 OH) were added into a 500 mL three-necked flask and mixed. 2 After three replacements, continue to maintain N 2 The reaction mixture was refluxed at 100 °C for 8 h under an atmosphere to carry out the hydrolysis, ring opening and polymerization process. Next, the temperature was lowered to 50 °C and vacuum was applied to remove the by-products methanol and water. This process helped to further promote the condensation of siloxane molecules. After the by-products were removed, the temperature was raised to 150 °C again and maintained for 30 min to remove Me 4 OH, and then treated at 170°C in vacuum for 2h to remove small molecular weight low boiling substances. Finally, the product was cooled to 25°C under reduced pressure to obtain a colorless viscous liquid aminopolysiloxane APDMS.
[0038] 7.2 g of acetic acid (HAc) and 72.8 g of deionized water were added to a 150 mL single-necked flask and kept warm at 5°C for 10 min. Then 20 g of APDMS was added dropwise to the HAc aqueous solution and stirred continuously at 5°C until the APDMS was completely dissolved. Finally, a clear APDMS-HAc aqueous solution was obtained and stored at 4°C for future use.
[0039] In a 250mL three-necked flask, PVA (10.0g) was dissolved in deionized water (40mL) and stirred in a 95℃ oil bath for 1h until the solution became clear. Then the PVA aqueous solution was cooled to room temperature and 50g of APDMS-HAc aqueous solution was added, and stirring was continued for 1h to make the mixed solution evenly dispersed. The mixed solution was poured into a mold and frozen at -20℃ for 21h, thawed at room temperature for 3h, and the process was repeated three times to obtain a PVA hydrogel. The obtained PVA hydrogel was soaked in a 0.1M sodium citrate (CA-Na) aqueous solution for 12h and the soaking solution was changed 3 times to form a polyacid fully cross-linked organosilicon network to obtain a polysilicone polyacid composite hydrogel recorded as PVA-APDMS 10 The resulting composite hydrogel was immersed in distilled water for three more days, and the water was changed six times to remove any residue.
[0040] Example 2
[0041] The difference from Example 1 is that the 0.1M sodium citrate aqueous solution is replaced by 0.1M sodium tripolyphosphate (TA-Na), and the obtained polysilicon polyacid composite hydrogel is recorded as PVA-APDMS. 10 -TA.
[0042] Example 3
[0043] The difference from Example 1 is that the 0.1M sodium citrate aqueous solution is replaced by 0.1M sodium phytate (PA-Na), and the obtained polysilicon polyacid composite hydrogel is recorded as PVA-APDMS. 10 -PA.
[0044] Comparative Example 1
[0045] PVA (10.0 g) was dissolved in deionized water (90 mL) in a 250 mL three-necked flask and stirred in a 95 °C oil bath for 1 h until the solution became clear. The PVA aqueous solution was poured into a mold and frozen at -20 °C for 21 h and thawed at room temperature for 3 h. After repeating this process three times, a PVA hydrogel was obtained, which was recorded as PVA. 10 The resulting PVA single-network hydrogel was then immersed in distilled water for three more days, with the water changed six times to remove any residue.
[0046] like Figure 1As shown, the polysilicone polyacid composite hydrogels of Examples 1 to 3 and the PVA hydrogel of Comparative Example 1 all have a uniform network structure, but the pore size of the PVA hydrogel is denser than that of the composite hydrogel. This is because there are molecular interactions such as hydrogen bonds between APDMS-HAc and PVA, which inhibit the crystallization and gelation of PVA and increase the pore size. Although the formation of the APDMS network increases the cross-linking density to a certain extent, it is not enough to compensate for the effect of molecular interactions on the structure. In addition, it is also found that the pore wall of the composite hydrogel is thicker than that of the pure PVA hydrogel, which may be caused by the formation of the APDMS network attached to the PVA network.
[0047] like Figure 2 As shown in a, compared with pure PVA hydrogel, the composite hydrogel has a -1 and 801cm -1 The stretching vibration and bending vibration peaks of Si-C are shown at 1080 cm -1 The Si-O stretching vibration peak is shown at , confirming the existence of the APDMS network. 10 -CA hydrogel at 1700 cm -1 The absorption peak of C=O is shown near PVA-APDMS 10 -TA and PVA-APDMS 10 -PA hydrogels have a peak at 1660 cm -1 and 1026cm -1 The stretching vibration absorption peaks of P=O and PO were shown, confirming that the polyacid successfully replaced HAc.
[0048] like Figure 2 As shown in Figures b and c, the storage modulus (G') of all hydrogels is greater than the loss modulus (G"), proving that these hydrogels have a self-supporting and stable network structure. The G' and G" of the composite hydrogel are significantly improved compared with the pure PVA hydrogel, indicating that the network structure of the composite hydrogel is further stabilized. However, the degree of modulus improvement of the composite hydrogels obtained by different polyacid substitution is different, as shown in PVA-APDMS 10 -PA hydrogel>PVA-APDMS 10 -TA hydrogel>PVA-APDMS 10 -CA hydrogel.
[0049] like Figure 3 As shown in a, the tensile strength of PVA hydrogel is only 0.23MPa, while that of PVA-APDMS 10 -CA hydrogel, PVA-APDMS 10 -TA hydrogel and PVA-APDMS 10-PA hydrogels have tensile strengths of up to 0.46MPa, 0.88MPa and 1.26MPa, respectively. Figure 3 (b) shows that the toughness of the composite hydrogel is much higher than that of the PVA hydrogel. Figure 3 Figures c to f show the loading-unloading cycle curves of the above hydrogels at 300% strain. The results show that the composite hydrogel has a larger hysteresis loop and higher energy dissipation efficiency than the PVA hydrogel. It is worth noting that PVA-APDMS, which has the highest energy dissipation efficiency, 10 -PA hydrogels have the highest tensile strength and toughness. Therefore, it is believed that the APDMS network enhances the mechanical properties of the composite hydrogels through efficient energy dissipation.
[0050] Example 4
[0051] Take octamethylcyclotetrasiloxane (D 4 , 74.0 g, 0.25 mol), N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (AEAPMDS, 88.7 g, 0.43 mol), deionized water (15.5 g, 0.86 mol) and tetramethylammonium hydroxide (0.05 g, Me 4 OH) were added into a 500 mL three-necked flask and mixed. 2 After three replacements, continue to maintain N 2 The reaction mixture was refluxed at 100 °C for 8 h under an atmosphere to carry out the hydrolysis, ring opening and polymerization process. Next, the temperature was lowered to 50 °C and vacuum was applied to remove the by-products methanol and water. This process helped to further promote the condensation of siloxane molecules. After the by-products were removed, the temperature was raised to 150 °C again and maintained for 30 min to remove Me 4 OH, and then treated at 170°C in vacuum for 2h to remove small molecular weight low boiling substances. Finally, the product was cooled to 25°C under reduced pressure to obtain a colorless viscous liquid aminopolysiloxane APDMS.
[0052] 7.2 g of acetic acid (HAc) and 72.8 g of deionized water were added to a 150 mL single-necked flask and kept warm at 5°C for 10 min. Then 20 g of APDMS was added dropwise to the HAc aqueous solution and stirred continuously at 5°C until the APDMS was completely dissolved. Finally, a clear APDMS-HAc aqueous solution was obtained and stored at 4°C for future use.
[0053] In a 250mL three-necked flask, PVA (10.0g) was dissolved in deionized water (77.5mL) and stirred in a 95℃ oil bath for 1h until the solution became clear. Then the PVA aqueous solution was cooled to room temperature and 12.5g of APDMS-HAc aqueous solution was added, and stirring was continued for 1h to make the mixed solution evenly dispersed. The mixed solution was poured into a mold and frozen at -20℃ for 21h, thawed at room temperature for 3h, and the process was repeated three times to obtain a PVA hydrogel. The obtained PVA hydrogel was soaked in a 0.1M sodium phytate (PA-Na) aqueous solution for 12h and the soaking solution was changed 3 times to form a polyacid fully cross-linked organosilicon network to obtain a polysilicone polyacid composite hydrogel recorded as PVA-APDMS 2.5 The resulting composite hydrogel was immersed in distilled water for three more days, and the water was changed six times to remove any residues.
[0054] Example 5
[0055] Different from Example 4, PVA (10.0 g) was dissolved in deionized water (65 mL), and 25 g of APDMS-HAc aqueous solution was added to obtain a polysilicon polyacid composite hydrogel, which was recorded as PVA-APDMS 5 -PA.
[0056] like Figure 4 As shown, for the polysilicon polyacid composite hydrogels of Examples 3 to 5, the higher the content of the APDMS network, the larger the hydrogel pore size and the thicker the pore wall. As analyzed above, the larger the pore size is because the introduction of the APDMS network inhibits the crystallization of PVA, and the thicker the pore wall is because the APDMS network interpenetrates with the PVA network and adheres to the PVA network. Figure 5 As shown in a, the peak intensities of Si-O, Si-C and PO increase with the increase of APDMS network content. Rheological results show that the modulus of the double network hydrogel also increases with the increase of APDMS network content ( Figure 5 b) in the above.
[0057] like Figure 6 As shown in the figure, the tensile strength, toughness and energy dissipation efficiency of the composite hydrogel are improved with the increase of the amount of APDMS network introduced. The APDMS network has a reversible non-covalent bond as a sacrificial bond. When the force is loaded, the sacrificial bond effectively dissipates energy through dissociation and recombination, thereby improving the mechanical properties of the hydrogel. The higher the APDMS network content, the more significant the energy dissipation effect ( Figure 7 ), the greater the improvement in mechanical properties. Figure 7Figure e shows the stress-strain curve of PVA-APDMS10-PA hydrogel after five continuous loading-unloading cycles at 300% strain. The first cycle has a large hysteresis loop, which decreases significantly from the second cycle. This is because the sacrificial bonds cannot be reorganized in such a short time. In addition, the hydrogel was continuously loaded-unloaded at different strains (50%-300%), showing a gradually increasing hysteresis loop ( Figure 7 f). This is because when the strain is small, the sacrificial bonds of the chemical bonds are not broken, but when the strain increases, the sacrificial bonds begin to break, and the greater the strain, the more sacrificial bonds are broken.
[0058] Example 6
[0059] Take octamethylcyclotetrasiloxane (D 4 , 74.0 g, 0.25 mol), N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (AEAPMDS, 88.7 g, 0.43 mol), deionized water (15.5 g, 0.86 mol) and tetramethylammonium hydroxide (0.05 g, Me 4 OH) were added into a 500 mL three-necked flask and mixed. 2 After three replacements, continue to maintain N 2 The reaction mixture was refluxed at 100 °C for 8 h under an atmosphere to carry out the hydrolysis, ring opening and polymerization process. Next, the temperature was lowered to 50 °C and vacuum was applied to remove the by-products methanol and water. This process helped to further promote the condensation of siloxane molecules. After the by-products were removed, the temperature was raised to 150 °C again and maintained for 30 min to remove Me 4 OH, and then treated at 170°C in vacuum for 2h to remove small molecular weight low boiling substances. Finally, the product was cooled to 25°C under reduced pressure to obtain a colorless viscous liquid aminopolysiloxane APDMS.
[0060] 7.2 g of acetic acid (HAc) and 72.8 g of deionized water were added to a 150 mL single-necked flask and kept warm at 5°C for 10 min. Then 20 g of APDMS was added dropwise to the HAc aqueous solution and stirred continuously at 5°C until the APDMS was completely dissolved. Finally, a clear APDMS-HAc aqueous solution was obtained and stored at 4°C for future use.
[0061] 25g of APDMS-HAc aqueous solution and 0.05g of photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were mixed into 75g of methacrylated gelatin (GelMA) aqueous solution (containing 5g of GelMA), and the solution was stirred for 0.5h to mix well. 2 Bubble for 0.5 h to remove dissolved oxygen in the mixed solution. Pour the mixed solution into a 24-well plate and then place it in a N 2The gelatin hydrogel was then irradiated with 365 nm UV (100 W) for 10 min under protection to form a white gelatin hydrogel. The gelatin hydrogel was then immersed in a 0.1 M sodium tripolyphosphate solution to crosslink the APDMS network to form a polysilicon polyacid composite hydrogel, which was recorded as GelMA. 5 +APDMS 5 -TA.
[0062] Example 7
[0063] Different from Example 6, 50 g of APDMS-HAc aqueous solution and 0.05 g of photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were mixed into 50 g of methacrylated gelatin (GelMA) aqueous solution (containing 5 g of GelMA), and the resulting polysilicon polyacid composite hydrogel was recorded as GelMA. 5 +APDMS 10 -TA hydrogel.
[0064] Example 8
[0065] Different from Example 6, 75 g of APDMS-HAc aqueous solution and 0.05 g of photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were mixed into 25 g of methacrylated gelatin (GelMA) aqueous solution (containing 5 g of GelMA), and the resulting polysilicon polyacid composite hydrogel was recorded as GelMA. 5 +APDMS 15 -TA.
[0066] Comparative Example 2
[0067] 0.05 g of photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone was added to 100 g of methacrylated gelatin (GelMA) aqueous solution (containing 5 g of GelMA), and the solution was stirred for 0.5 h to mix well. 2 Bubble for 0.5 h to remove dissolved oxygen in the mixed solution. Pour the mixed solution into a 24-well plate and then place it in a N 2 The gelatin was irradiated with 365 nm UV (100 W) for 10 min under protection to form a white gelatin hydrogel, which was labeled as GelMA. 5 .
[0068] like Figure 8 As shown in Figure 2, the presence of the APDMS network has little effect on the pore size of the gelatin network, and it is attached to the pore wall of the gelatin network. When the APDMS network content reaches 15wt.%, the gelatin network is buried and invisible. Fig. 9 As shown, GelMA 5 +APDMS10 -TA has a uniform element distribution, in which the presence of Si and P elements confirms the formation of an APDMS network.
[0069] like Fig.10 As shown in a, the higher the APDMS network content, the more opaque the hydrogel becomes. Fig.10 As shown in Figure b, the FT-IR results show that the absorption peak areas of Si-O, Si-C and PO increase with the increase of the content of the APDMS network. Fig.10 The rheological results shown in (c) indicate that the modulus of the composite hydrogel also increases with the increase in the content of the APDMS network, proving that the hydrogel becomes increasingly tough.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a polysilicone polyacid composite hydrogel, characterized in that: The following steps are involved: S1, adding aminopolysiloxane to an organic acid solution, stirring until the aminopolysiloxane is dissolved, and obtaining a hydrophilic polysilicon organic acid salt aqueous solution; S2, mixing a hydrophilic polysilicon organic acid salt aqueous solution with a hydrogel matrix to obtain a mixed solution, cross-linking the mixed solution to obtain a single network hydrogel, and immersing the single network hydrogel in an aqueous solution of a polyacid salt to obtain a polysilicon polyacid composite hydrogel.
2. The preparation method according to claim 1, characterized in that In step S1, the organic acid includes acetic acid, and the mass ratio of the organic acid to aminopolysiloxane is (0.1-2):
1.
3. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of amino group to silicon atom in the aminopolysiloxane is (0.1-1):
1.
4. The preparation method according to claim 1, characterized in that: In step S2, the hydrogel matrix includes PVA, gelatin or methacrylated gelatin, the mass concentration of aminopolysiloxane in the mixed solution is 1-10wt.%, and the mass concentration of the hydrogel matrix is 1-15wt.%.
5. The preparation method according to claim 1, characterized in that: In step S2, the cross-linking method includes freeze-thaw cycle, light initiation or heat initiation.
6. The preparation method according to claim 5, characterized in that: The freeze-thaw cycle is specifically placed in an environment of -25°C to 0°C for 1 to 24 hours and then placed in an environment of 0°C to 35°C for 1 to 4 hours, and repeated 1 to 5 times.
7. The preparation method according to claim 5, characterized in that: The photoinitiator used for photoinitiation includes 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and the mass of the photoinitiator is 0.5% to 2% of the mass of the hydrogel matrix.
8. The preparation method according to claim 1, characterized in that: The polyacid salt includes at least one of sodium salt, potassium salt and lithium salt of a polyacid, and the polyacid includes at least one of citric acid, tripolyphosphoric acid and phytic acid.
9. A polysilicone polyacid composite hydrogel, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the polyorganosilicon polyacid composite hydrogel according to claim 9 in the field of structural materials, photoluminescent devices, intelligent switches, drivers or biomedical materials.
Citation Information
Cited By
High-damping organic silicon-based composite hydrogel as well as preparation method and application thereof
CN120923819A